Studying the Properties of Polyvinyl Alcohol/Cellulose Nanofiber/Hydroxyapatite Hybrid Nanocomposite - Mostafa Yahyavi; Aboulghasem Khazaeian; Mahdi Mashkour (علوم و تکنولوژی پلیمر, 2015)
Nanocomposite materials have recently attracted much attention because of their desirable and unique physical and mechanical properties. Today, many studies have focused on the preparation of high performance new nanocomposites made of biobased and biodegradable materials as both the matrix and reinforcement phases. Because of biocompatibility, biofunctionality, and biological safety in the body, hydroxyapatite-polyvinyl alcohol composites are vastly used in medical applications, specially in the bone tissue regeneration. The properties of a new generation of nanocomposites consisting of hydroxyapatite nanoparticles and cellulose nanofibers, dispersed in polyvinyl alcohol matrix, were investigated. The percentage by weight of each component in the final formulation and the time of ultrasonication were studied as factors affecting the physical and mechanical properties. Tensile strength, elastic modulus and resistance to water dissolution were evaluated. The results showed that by increasing the percentage by weight of PVA and cellulose nanofibers and ultrasonication time, the tensile strength and elastic modulus increased and the resistance to water dissolution and weight loss decreased. On the other hand, with increasing the amount of hydroxyapatite nanoparticles in the final formulation, the elastic modulus and resistance to water solubility increased, while the tensile strength decreased significantly. Scanning electron microscopy (SEM) micrographs were used to find exact correlations between the observed physical and mechanical properties and the structural morphology.